2005
DOI: 10.1080/10715760500231836
|View full text |Cite
|
Sign up to set email alerts
|

Rosmarinic acid inhibits the formation of reactive oxygen and nitrogen species in RAW264.7 macrophages

Abstract: Antioxidant action of Rosmarinic acid (Ros A), a natural phenolic ingredient in many Lamiaceae herbs such as Perilla frutescens, sage, basil and mint, was analyzed in relation to the Ikappa-B activation in RAW264.7 macrophages. Ros A inhibited nitric oxide (NO) production and inducible nitric oxide synthase (iNOS) protein synthesis induced by lipopolysaccharide (LPS), and also effectively suppressed phorbol 12-myristate 13-acetate (PMA)-induced superoxide production in RAW264.7 macrophages in a dose-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(70 citation statements)
references
References 17 publications
2
65
0
Order By: Relevance
“…Additional studies have shown that RA eff ectively inhibited ROS-mediated damage in astrocytes and macrophages (Gao et al, 2005;Qiao et al, 2005). Furthermore, other studies suggested that RA may prevent apoptosis in cardiac muscle cells (Kim et al, 2005), PC12 cells (Iuvone et al, 2006), and human dopaminergic neuronal cells (Lee et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…Additional studies have shown that RA eff ectively inhibited ROS-mediated damage in astrocytes and macrophages (Gao et al, 2005;Qiao et al, 2005). Furthermore, other studies suggested that RA may prevent apoptosis in cardiac muscle cells (Kim et al, 2005), PC12 cells (Iuvone et al, 2006), and human dopaminergic neuronal cells (Lee et al, 2008).…”
Section: Discussionmentioning
confidence: 95%
“…These reactive nitrogen species can have toxic effect on mitochondria and cause damage to macromolecules, such as DNA, proteins, and lipids. A recent study has shown that Ros A can also act as an effective protector against peroxynitrite-mediated damage and as a potent inhibitor of superoxide and NO synthesis; inhibition of ROS and reactive nitrogen species formation is achieved partly by the ability of Ros A to inhibit serine phosphorylation of Iκ-Bα, an inhibitor of the transcription factor NF-κB (Qiao et al, 2005). Therefore, precise regulation of superoxide and NO production appears to be critical for the survival of islet grafts in our model.…”
Section: Discussionmentioning
confidence: 99%
“…Cell growth inhibition of mimosine was determined by MTT reduction assay as previously described [36]. C6 glioma cells plated in 96-well plates were treated with mimosine at different concentrations (50-500 lM).…”
Section: Measurement Of Cell Viabilitymentioning
confidence: 99%